2006
DOI: 10.1088/0953-8984/18/17/l01
|View full text |Cite
|
Sign up to set email alerts
|

Real-time coverage monitoring of initial oxidation processes on Si(001) by means of surface differential reflectance

Abstract: Initial oxidation processes on Si(001) have been studied by means of surface differential reflectance (SDR). The time courses of the SDR spectra measured during thermal oxidation at 820 and 920 K allowed two different growth modes, Langmuir-type adsorption and two-dimensional island growth, to be distinguished. No photon energy dependence was observed in the time course of the SDR intensity at either temperature. On the other hand, different uptake curves were observed at different photon energies for oxidatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
16
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 37 publications
4
16
0
Order By: Relevance
“…8 Our results may indicate that this trend is also the case for the transition temperature between Langmuir-type adsorption and two-dimensional island growth. In our previous study with SDR, we demonstrated that the SDR signal is proportional to the total oxygen coverage above 820 K. 9 The transition temperature obtained with SDR at the same oxidation pressure of 1.0ϫ 10 −5 Pa is between 820 and 920 K and consistent with the present results.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…8 Our results may indicate that this trend is also the case for the transition temperature between Langmuir-type adsorption and two-dimensional island growth. In our previous study with SDR, we demonstrated that the SDR signal is proportional to the total oxygen coverage above 820 K. 9 The transition temperature obtained with SDR at the same oxidation pressure of 1.0ϫ 10 −5 Pa is between 820 and 920 K and consistent with the present results.…”
Section: Discussionsupporting
confidence: 92%
“…6 This transition of the monolayer regime has been further studied with AES both at 2.7ϫ 10 −5 and at 3.7ϫ 10 −4 Pa. 6 Our recent study at the relatively low pressure of 1.0ϫ 10 −5 Pa with real-time SDR showed that the two growth modes, Langmuir-type adsorption and two-dimensional island growth, can be distinguished from the uptake curves for monolayer oxidation with this technique, as with other spectroscopic methods. 9 This result confirmed the feasibility of using such an optical method to estimate the coverage of adsorbates with the same precision as AES.…”
Section: Introductionsupporting
confidence: 69%
See 3 more Smart Citations